Comparison of the Clinical Expression of Patients with Enthesitis/Spondylitis-Related Juvenile Idiopathic Arthritis (E/SpRJIA) from Türkiye and India - Rana İşgüder; Avinash Sharma; Zehra Kızıldağ; Yağmur Bayındır; Zeynep Balık; Ümit Gül; Cüneyt Karagöl; Şeyma Türkmen; Taner Coşkuner; Sandesh Guleria; Gülçin Aytaç; Pratap Kumar Patra; et al. (Archives of Rheumatology, 2026)
Background/Aims: To compare the clinical characteristics of enthesitis/ spondylitis-related juvenile idiopathic arthritis (E/SpRJIA), a relatively prevalent JIA subtype in Türkiye and India, and to explore potential populationspecific differences in disease expression. Materials and Methods: This multicenter, binational, retrospective cohort study included children fulfilling the provisional PRINTO classification criteria for E/SpRJIA from 12 pediatric rheumatology centers in Türkiye and India. Demographic characteristics, clinical manifestations, human leukocyte antigen B27 (HLA-B27) status, laboratory findings, disease course, and treatment-related data were collected. A multivariable logistic regression analysis was performed to identify factors independently associated with sacroiliitis at diagnosis. Results: A total of 498 patients were included (391 Turkish and 107 Indian). At disease onset, peripheral polyarticular involvement was more common in Indian patients (40.2% vs 5.6%), whereas axial involvement was more frequent in Turkish patients (45.8% vs 18.7%). HLA-B27 positivity was higher in Indian patients than in Turkish patients (79.5% vs 56.4%). During follow-up, sacroiliitis, enthesitis, and tarsitis were more common among Turkish patients, while peripheral arthritis and dactylitis were more frequent among Indian patients. NSAIDs were used more frequently in India, whereas conventional and biologic DMARDs were more commonly used in Türkiye. In multivariable analysis, country of origin remained independently associated with sacroiliitis at diagnosis, whereas HLA-B27 positivity did not. Conclusion: E/SpRJIA demonstrates substantial phenotypic heterogeneity between Turkish and Indian populations. Turkish patients exhibited a predominantly axial disease pattern, whereas Indian patients more commonly showed peripheral polyarticular involvement despite higher HLA-B27 positivity. These findings suggest that factors beyond HLA-B27, including broader genetic, environmental, and population-specific influences, may contribute to differences in disease expression. Further prospective and genetically informed studies are needed to clarify the determinants of this heterogeneity. Cite this article as: İşgüder R, Sharma A, Kızıldağ Z, et al. Comparison of the Clinical Expression of Patients with Enthesitis/Spondylitis-Related Juvenile Idiopathic Arthritis (E/SpRJIA) from Türkiye and India. ArchRheumatol. Published online September 1, 2026. doi: 10.5152/ArchRheumatol.2026.25122.